Shopping Plaza in Bengkayang Regency with an Organic Architecture Approach - Vedro, Kristoforus; Setyowati, Wiwit; Wibowo, Ardiyan Adhi; Nugradi, Didik Nopianto Agung; Savanti, Fisa (Universitas Negeri Semarang, 2024)
The development of a city is influenced by local factors such as population size, socio-economic aspects, and culture. Collaboration between the government, stakeholders, and the community is essential to ensure sustainable urban growth. The construction of modern shopping centers has significant impacts, including boosting the local economy, increasing residents' income, promoting tourism, and enhancing infrastructure. Although Bengkayang Regency holds great economic potential, it currently lacks a modern shopping center. Therefore, building a modern shopping plaza is crucial to support economic growth and improve the well-being of the local community. The goal of designing the shopping plaza is to accommodate the daily needs, entertainment, and lifestyle of Bengkayang Regency's residents with a modern design that blends seamlessly with nature. The proposed site is located in Sebopet Village, Bengkayang District, Bengkayang Regency, West Kalimantan. The site is situated near the Bengkayang traditional market and government center but not too close to residential areas. To achieve these objectives, various methods are applied, including site surveys, literature reviews, and precedent studies of shopping centers. The design incorporates the principles of organic architecture, aiming to create environmentally friendly spaces that harmonize with nature. Key elements of the organic architecture approach include Building as Nature, Form Follows Flow, Of the People, Of the Materials, Youthful and Unexpected, and Living Music. With the application of these principles, the shopping center is expected to serve as a comprehensive space that provides both physical and non-physical benefits, while also contributing to local economic development.